Synthesis, crystal structure and luminescent properties of isoreticular lanthanide–organic frameworks based on a tetramethyl-substituted terphenyldicarboxylic acid. (15th January 2021) - Dascălu, Ioan-Andrei; Mikhalyova, Elena A.; Shova, Sergiu; Bratanovici, Bogdan-Ionel; Ardeleanu, Rodinel; Marangoci, Narcisa; Lozan, Vasile; Roman, Gheorghe
Graphical abstract: A series of isoreticular lanthanide–organic frameworks derived from a lengthy dicarboxylate ligand with a terphenyl core have been synthesized and characterized. Evaluation of their luminescence showed that the Tb 3+ -MOF has an expected emission quantum yield of 98%. Highlights: Solvothermal synthesis of lanthanide–organic frameworks is reported. Single crystal X-ray structures were established for six coordination polymers. These isoreticular networks include nitrate, water and DMF in their structure. Luminescent properties of these MOFs have been investigated. Tb(III)-based MOF has an expected emission quantum yield of 98%. Abstract: A series of 3D metal–organic frameworks derived from 2′, 3′, 5′, 6′-tetramethyl-[1, 1′:4′, 1′′-terphenyl]-4, 4′′-dicarboxylic acid (H2 L) as organic linker and various lanthanides have been prepared. The resulting coordination polymers [Ln3 L4 (NO3 )(DMF)x (H2 O)]n (where x = 2 or 3) were characterized by elemental analysis, thermogravimetric investigations, IR and TG-FTIR spectroscopy, as well as powder X-ray diffraction measurements. The crystal structure for six of these isostructural networks based on La(III), Ce(III), Nd(III), Sm(III), Tb(III) and Dy(III) was established using single crystal X-ray crystallography. As an example, the asymmetric part of [La3 L4 (NO3 )(DMF)3 (H2 O)]n consists of two deprotonated ligand molecules L 2- and two La(III) ions, one of them occupying a general position with full site occupancy, while the other one has a fractional occupancy of 0.5. Investigation of the luminescence of these coordination polymers showed that compounds containing La 3+, Nd 3+ and Gd 3+ possess only the emission associated with the anion of the organic ligand (L 2- ), polymers containing Eu 3+ and Tb 3+ show pure metal-centered radiation, while networks containing Dy 3+ and Sm 3+ display dual metal- and ligand-centered luminescence. The organic linker acts as a good antenna for Tb 3+, Eu 3+, Dy 3+ and Sm 3+ ions.